Enhancing High School Students' Critical Thinking and Collaboration Skills on the Topic of Viruses Through the Service-Learning Model - Ramadhan, Ahmad Naharuddin; Antasari, Galuh Ajeng; Fitarahmawati; Antony, Muhammad Khoirul; Pradana, Sendy Putra (Jurnal Penelitian Pendidikan, 2025)
Strengthening critical thinking and collaboration skills has become an urgent need in 21st-century education; however, these skills remain relatively low among students. In fact, both are essential for navigating complex information, solving real-world problems, and working effectively in diverse teams. This study aims to examine the effectiveness of the service-learning model in enhancing the critical thinking and collaboration skills of tenth-grade students, as well as to investigate the correlation between these two skills in the context of a virus-related biology topic. A quasi-experimental design with a non-equivalent pretest-posttest control group was employed. The sample consisted of two classes (30 students each), selected using cluster sampling. Critical thinking skills were assessed through tests, while collaboration skills were measured using observation sheets. Data were analyzed using independent sample t-tests and Pearson correlation. The results showed that the service-learning model was effective in improving both critical thinking and collaboration skills, and there was a significant positive correlation between the two. The novelty of this study lies in the integration of the service-learning model into biology instruction on the topic of viruses, aiming to foster 21st-century skills through meaningful, experience-based learning approaches.